Identification of potential hub genes linked to immune and metabolic alterations in postoperative systemic inflammatory dysregulation - Cao, Silu; Tang, Jinxuan; Fei, Miaomiao; Jing, Qi; Meng, Fanbing; Zhang, Meixian; Liu, Qidong; Zhang, Hui; Li, Cheng (Frontiers in Immunology, 2023)
Background: Postoperative systemic inflammatory dysregulation is characterised by strongly interlinked immune and metabolic abnormalities. However, the hub genes responsible for the interconnection between these two systemic changes remain to be identified.We analysed the differentially expressed genes (DEGs) and biological functions of individual peripheral blood nucleated cells in patients with postoperative systemic inflammatory dysregulation (PSID) (n = 21, CRP > 250 mg/L) and control patients (n = 25, CRP < 75 mg/L) following major abdominal surgery. Correlation analysis was used to explore the interconnections of immune-related DEGs (irDEGs) and metabolism-related DEGs (mrDEGs). Two methods were used to screen hub genes for irDEGs and mrDEGs. We screened the hub genes between DEGs using 12 algorithms with Cytohubba in Cytoscape, and the hub immune-related and metabolicrelated genes using weighted gene co-expression network analysis. The hub genes selected were involved in the interaction between changes in the immunity and metabolism of PSID. Finally, we validated our results in mice with PSID to confirm our results.We identified 512 upregulated and 254 downregulated DEGs in patients with PSID compared with controls. Gene enrichment analysis revealed that DEGs were significantly associated with immune-and metabolism-related biological processes and pathways. Correlation analysis revealed a close association between irDEGs and mrDEGs. Fourteen unique hub genes were screened using 12 algorithms in CytoHubba in Cytoscape and weighted gene co-expression network analyses. Among them, CD28, CD40LG, MAPK14, and S100A12 were selected as hub genes for both immune-and metabolism-related genes, which play a critical role in the interaction between changes in immunity and metabolism in PSID. The experimental results also showed that the expression of these genes was significantly altered in PSID mice.This study identified hub genes associated with immune and metabolic alterations in patients with PSID and hub genes that linked them. These findings provide novel insights into the mechanisms underlying immune and metabolic interactions and propose new targets for clinical treatment.